Planting Tolerance Characters for Class VI Students in Elementary Schools in Wates District, Blitar Regency: Penanaman Karakter Toleransi Siswa Kelas VI di Sekolah Dasar di Kecamatan Wates Kabupaten Blitar - Hengky Erwanda Putra; Machful Indra Kurniawan (Academia Open, 2021)
This research is based on field results that the tolerance character of class VI students at SDN Tulungrejo 04, Wates District, Blitar Regency has not been maximized. The purpose of this study was to describe the teacher's efforts in instilling the tolerance character of sixth grade students at SDN Tulungrejo 04, Wates District, Blitar Regency and to describe the supporting and inhibiting factors in instilling the tolerance character of sixth grade students at SDN Tulungrejo 04 Wates District, Blitar Regency. Data analysis was carried out using the Miles and Huberman model field analysis. The results showed that efforts to cultivate the character of tolerance were carried out by inviting students to respect each other with all parties and pray according to their respective beliefs. The results also show that the supporting factors in instilling the character of tolerance in students are students' willingness, coordination between teachers and students, and the existence of rules from the school to instill tolerance in students. While the inhibiting factor in efforts to cultivate the character of tolerance in students is the willingness of students and the nature of students who differ from one student to another. Keywords: Character, Tolerance, Students